2022
DOI: 10.1007/s10660-022-09635-8
|View full text |Cite
|
Sign up to set email alerts
|

Online customer engagement in the post-pandemic scenario: a hybrid thematic analysis of the luxury fashion industry

Abstract: The COVID-19 pandemic had a strong impact on all businesses, and especially the luxury sector. As an adaptation strategy, businesses are engaging in a digital transformation, moving all or most of their activities to online platforms. However, the nature of the luxury industry, deeply rooted in exclusivity and a high degree of human contact, is at odds with the mass-oriented, accessible, and automated nature of e-commerce, thus raising concerns about this industry's ability to reap the benefits of digital tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The literature suggested the innovation through digitalization and how luxury product manufacturers and service providers manage their organizations. Hoang et al (2022) suggested that organizations should restructure the enterprise's team structure from the traditional e-commerce team to a matrix team that works based on the customers' segments. Asian et al (2020) suggested that luxury products companies, especially luxury sports goods (LSG) companies, should conduct innovation in their supply chain by applying the risk-sharing and coordinating roles of flexible trade credit contracts to generate optimal decisions of wholesalers and LSG suppliers.…”
Section: Online Landscapementioning
confidence: 99%
See 3 more Smart Citations
“…The literature suggested the innovation through digitalization and how luxury product manufacturers and service providers manage their organizations. Hoang et al (2022) suggested that organizations should restructure the enterprise's team structure from the traditional e-commerce team to a matrix team that works based on the customers' segments. Asian et al (2020) suggested that luxury products companies, especially luxury sports goods (LSG) companies, should conduct innovation in their supply chain by applying the risk-sharing and coordinating roles of flexible trade credit contracts to generate optimal decisions of wholesalers and LSG suppliers.…”
Section: Online Landscapementioning
confidence: 99%
“…To induce the consumption of sustainable luxury products, the manufacturers should show the intangibility of the sustainability of their products by showing the related certificate or animal testing-free product guarantee (Hoang et al, 2022).…”
Section: Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the conventional wisdom suggests that the luxury industry has not significantly benefited from social media due to the inherent nature of luxury brands, which are characterized as exclusive, scarce and prestigious, contradicting social media's attribute of mass access. In addition, the personalized physical interactions and services received in physical stores, which are essential to the luxury experience, are deemed unlikely to be replicated in an online setting (Hoang et al, 2022). In order to obtain a nuanced picture of the scenario, the present study strives to probe this phenomenon to examine the impact of social media communication and social media engagement on luxury brand outcomes.…”
Section: Introductionmentioning
confidence: 99%